Emotional value : creating strong bonds with your customers - Barlow, Janelle, 1943- (Berrett-Koehler Publishers, 2000)
Combining strategic advice with wisdom found in books such as Daniel Goleman's "Working with Emotional Intelligence, " two international management consultants outline ways in which businesses can elevate levels of satisfaction.